Progress towards precision medicine for lupus: The role of genetic biomarkers (2018)
Systemic lupus erythematosus (SLE) is the prototypical systemic autoimmune disease (AD). Precision medicine gives clinicians and society access to the information needed to create individually tailored programs to predict, prevent, and treat SLE. Although several biomarkers have been described for SLE, current expansion of knowledge on lupus genetics makes the implementation of genetic biomarkers possible. Herein, a comprehensive description of relevant SLE genetic biomarkers from the precision medicine perspective is offered. National inception cohorts should be created and the implementation of translational programs for the control of ADs such as SLE should be put into practice. Factors that are predictive of developing these conditions should be examined at the population level in order to establish preventive measures in at-risk individuals for whom healthcare should be personalized/precise and participatory. The implementation of such a program will allow the discovery of new mechanisms and a new taxonomy of ADs. The translational model should also involve educational and training programs together with digital participatory surveillance systems. Healthcare’s one-size-fits-all approach to treating patients will be replaced with a personalized/precision approach to medicine that focuses on individuals and each family member. © 2018 Informa UK Limited, trading as Taylor and Francis Group.